Executive Committee Minutes 2010-03-04 - Academic Senate:::::::::
Arts and Humanities GE Reform, Solano Liberal Arts Program, Resolution endorsing plan to utilize SSU faculty expertise local government & Resolution endorsing campus fiscal transparency, Resolution opposing expansion of WalMart